The Effect of Work Stress, Emotional Intelligence and Work Life Balance on Job Satisfaction (Case Study on Cooperative Employees in Ponorogo Regency) - Septian Wahyu Adit Pratama; Sri Hartono; Yusup arip (Journal of Creative Power and Ambition (JCPA), 2026)
Job satisfaction is a crucial factor influencing employee performance, organizational commitment, and the long-term sustainability of savings and loan cooperatives, particularly those facing challenges related to non-performing loans. High workloads and financial pressures may increase employees' work stress, making emotional intelligence and work-life balance important factors in maintaining job satisfaction. This study aimed to examine the effects of work stress, emotional intelligence, and work-life balance on the job satisfaction of cooperative employees in Ponorogo Regency. A quantitative survey approach was employed involving 100 employees selected through purposive sampling from savings and loan cooperatives and cooperatives with credit financing units. Data were collected using a five-point Likert scale questionnaire and analyzed with multiple linear regression using IBM SPSS Statistics Version 27. The results revealed that work stress negatively and significantly affects job satisfaction, whereas emotional intelligence and work-life balance have positive and significant effects. Simultaneously, all three variables significantly influence job satisfaction. These findings highlight the importance of reducing work stress while strengthening employees' emotional intelligence and promoting a healthy work-life balance to improve job satisfaction and support sustainable organizational performance.